Pengaruh Language Games Terhadap Kemampuan Berbicara Bahasa Inggris Mahasiswa Administrasi Bisnis Internasional Politeknik Kampar - Dzulhijjah Yetti; Rahmad Akbar; Merlia Rahmayani; Andri Nofiar. Am; Antoni Pribadi (Guruku: Jurnal Pendidikan dan Sosial Humaniora, 2023)
In the process of language learning, particularly English, there are various methods and strategies that can be applied. One interesting approach is through language games. This study aims to examine the impact of using language games on students' English-speaking skills. The subjects of the study involved 19 students from classes 1 to 4 of the International Business Administration Program at Kampar Polytechnic. The results revealed that the use of language games significantly improved students' speaking abilities, including pronunciation, fluency, and sentence accuracy. Additionally, student participation, discipline, and responsiveness also showed improvement. Based on the questionnaire results, all students agreed that language games were not only enjoyable but also highly motivating, encouraging them to engage more actively in class activities.